2020
DOI: 10.1177/1526602820914618
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Scoring Balloons on Percutaneous Transluminal Angioplasty Outcomes in Femoropopliteal Lesions

Abstract: Purpose: To investigate the efficacy of scoring balloons for immediate success of percutaneous transluminal angioplasty (PTA) in femoropopliteal lesions. Materials and Methods: Between 2013 and 2019, 398 consecutive patients with de novo femoropopliteal lesions were treated using PTA in our hospital. The procedure success rate was compared among patients undergoing PTA with vs without scoring balloons after 1:1 propensity score matching on hemodialysis, TransAtlantic Inter-Society Consensus II classification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Vessel preparation with special balloons, as compared to conventional balloons, has recently been reported to be useful in achieving a larger acute gain in calcified lesions. 23 However, our results suggested that a larger acute gain might not directly improve vascular patency after DCB treatment of calcified lesions, and thus, careful postintervention follow-up is necessary.…”
Section: Discussionmentioning
confidence: 68%
“…Vessel preparation with special balloons, as compared to conventional balloons, has recently been reported to be useful in achieving a larger acute gain in calcified lesions. 23 However, our results suggested that a larger acute gain might not directly improve vascular patency after DCB treatment of calcified lesions, and thus, careful postintervention follow-up is necessary.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, this study found that the severity of calcification, as graded by the Peripheral Artery Calcium Scoring System, CTOs, and long lesions did not impact technical success, suggesting that the scoring element of the balloons used in this study was effective in treating complex lesions, consistent with the results of a previous study. 9 Drug-coated balloons (DCBs) have consistently demonstrated improved efficacy compared with standard balloon angioplasty in treating femoropopliteal lesions. [1][2][3] As such, DCB angioplasty is recommended as the first-line treatment for femoropopliteal lesions instead of uncoated balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Some would suggest that cutting balloons, which longitudinally score the vessel, are more effective than any others, as they better prepare the vessel prior to stenting and thus help to reduce restenosis rates (Lee et al, 2002). However, some studies have shown that cutting balloons are not effective for TASC II type D lesions (Horie et al, 2020). Therefore, by creating a biomimetic with calcium deposits printed in a ceramic material, which more closely resembles the mechanical properties of true CTO calcification, there is potential to further investigate the interactions of current cutting balloons with severe calcification and improve their design so that they may be utilised for clinical treatment of such lesions in future.…”
Section: Discussionmentioning
confidence: 99%